Exploring anxiety symptoms, coping strategies, and socio-demographic influences among myocardial infarction patients in a tertiary care setting - Mohammad Sabeeh Ul Haq; Dua Nilofar Jawed; Nehrish Patel; Waqar Khan; Aisha Alamgir; Shagufta Yamin; Rabia Anwar; Tafazzul Hyder Zaidi; Munawar Khursheed (PLoS ONE, 2025)
Objective This study aimed to investigate levels of anxiety/anxiety symptoms and coping methods employed among patients suffering from myocardial infarction admitted in a tertiary care setting in a developing country. It also aimed to study the relationship of anxiety levels and coping strategies with each other and also the influence of various socio-demographic factors on anxiety levels and coping strategies used by the patients. Methods A cross-sectional study was conducted at National Institute of Cardiovascular Disease (NICVD), Karachi, Pakistan involving 203 patients diagnosed with myocardial infarction. Sampling was conducted by non-probability convenience method. Patients were asked to fill a questionnaire comprising a socio-demographic form, HAM – A scale for anxiety symptoms and brief COPE scale for coping methods. Statistical analysis was performed using independent t-test, ANOVA, MANOVA, Pearson correlation and multiple regressions. Results Study comprised 203 patients (134 male, 69 female), 36.9% of the patients showed anywhere from moderate to severe levels of anxiety. Gender, history of myocardial infarction, family visits and hospital satisfaction were found to have statistical significance in influencing mean HAM – A scores among the population. Significant differences in problem focused coping was found among different gender and socio economic classes, while avoidance focused coping differences were found between patients receiving family visits and drug users as well as perceived hospital satisfaction. Hospital satisfaction also influenced emotional focused coping. Conclusion This research highlights the importance of providing integrated psychological support for patients with myocardial infarction, specifically on anxiety and coping methods. By examining these factors, we can better understand how they influence mental health outcomes. Addressing anxiety and enhancing effective coping strategies are crucial for improving overall recovery and quality of life for these patients.